TriticeaeSSRdb: a comprehensive database of simple sequence repeats in Triticeae - Li, Tingting; Cai, Shaoshuai; Cai, Zhibo; Fu, Yi; Liu, Wenqiang; Zhu, Xiangdong; Lai, Chongde; Cui, Licao; Pan, Wenqiu; Li, Yihan (Frontiers in Plant Science, 2024)
Microsatellites, known as simple sequence repeats (SSRs), are short tandem repeats of 1 to 6 nucleotide motifs found in all genomes, particularly eukaryotes. They are widely used as co-dominant markers in genetic analyses and molecular breeding. Triticeae, a tribe of grasses, includes major cereal crops such as bread wheat, barley, and rye, as well as abundant forage and lawn grasses, playing a crucial role in global food production and agriculture. To enhance genetic work and expedite the improvement of Triticeae crops, we have developed TriticeaeSSRdb, an integrated and user-friendly database. It contains 3,891,705 SSRs from 21 species and offers browsing options based on genomic regions, chromosomes, motif types, and repeat motif sequences. Advanced search functions allow personalized searches based on chromosome location and length of SSR. Users can also explore the genes associated with SSRs, design customized primer pairs for PCR validation, and utilize practical tools for whole-genome browsing, sequence alignment, and in silico SSR prediction from local sequences. We continually update TriticeaeSSRdb with additional species and practical utilities. We anticipate that this database will greatly facilitate trait genetic analyses and enhance molecular breeding strategies for Triticeae crops. Researchers can freely access the database at http://triticeaessrdb.com/.